2023
DOI: 10.3390/f14020248
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Responses of European Beech (Fagus sylvatica L.) to Drought Intensity and Length—A Review of the Impacts of the 2003 and 2018–2019 Drought Events in Central Europe

Abstract: A combined severe heatwave and drought, starting in 2018 and lasting for several months, restarted the discussion on the resistance of European beech to climatic changes, with severe growth reductions, early leaf senescence, leaf browning, and diebacks reported across Central Europe. These responses may result in long-term impacts such as reduced vitality of beech, especially under potential future drought periods. While the 2003 drought caused severe crown damage and defoliation and a loss in vitality, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…The latest research shows that recent droughts have seriously impacted beech forests [17][18][19]. Depleted soil moisture conditions during drought can significantly affect tree physiology, affecting tree growth and mortality rates [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The latest research shows that recent droughts have seriously impacted beech forests [17][18][19]. Depleted soil moisture conditions during drought can significantly affect tree physiology, affecting tree growth and mortality rates [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…3, 6) may be linked to the 2003 drought but are far surpassed by recent declines. In line with these findings, several studies reported that the impacts on forest ecosystems during the 2003 drought were superseded by those of the drought in 2018/2019 (Buras et al 2020, Schnabel et al 2022, Rukh et al 2023. Forests have the capacity to mitigate the direct effects of extreme weather and shorter-term droughts (Davis et al 2019, Gohr et al 2021).…”
Section: Non-linear Abundance and Biomass Trends Are Linked To Long-t...mentioning
confidence: 79%
“…Nevertheless, forest ecosystems are increasingly under pressure by climate change (Oakes et al 2014, Seidl et al 2017, Senf et al 2018, Martinez del Castillo et al 2022). Recent droughts in 2003 and in 2018/2019 had significant negative impacts on European temperate forests (Senf et al 2020, Senf and Seidl 2021, Schnabel et al 2022, Rukh et al 2023) and were followed by another drought in 2022, which has recently been described as unprecedented in 500 years (Schumacher et al 2023, Henley 2022). These events potentially had large effects on biodiversity in general (Archaux and Wolters 2006) and on insects in particular (Pureswaran et al 2018, Gely et al 2020, Cours et al 2023, Blüthgen et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Legacy of a drought event in forests can take many forms (Müller & Bahn 2022, Rukh et al 2023, depending on the tree demography most influenced. The mortality of adult trees can create opening in a forest, influencing the long-term profitability of an economic forest but also the carbon and water cycle and species composition.…”
Section: Drought Legacy Effects In Foreststhe Accumulation Of Long Te...mentioning
confidence: 99%